Practitioners' perspectives and needs: Developing skills to support unaccompanied asylum‐seeking children (UASCs) in experiencing 'belonging' in English educational spaces. (14th October 2021) - Ward, Catherine
Abstract : This article builds on Yuval‐Davis's (2006, 2007, 2011) theories of belonging, in order to relay how practitioners can support unaccompanied asylum‐seeking children (UASCs) in developing a positive sense of belonging in educational spaces in England. To do so, the article synthesises literature surrounding theories of belonging, UASCs' educational access in England and practices supporting UASCs' educational attainment and sense of belonging. Further, the article considers interviews with a social worker, English for speakers of other languages (ESOL) teacher, charity sector staff member, legal expert and government workers in East England, all of whom work with UASCs. Interview analysis seeks to understand how practitioners believe UASCs find a sense of belonging in the educational spaces that they inhabit. After presenting the interview findings, the article builds on scholarly literature related to supporting UASCs' education by discussing how practitioners, including all staff who interact with UASCs in school, college or residential accommodation spaces, can work to facilitate UASCs' sense of belonging in educational spaces in England. The article recognises that practitioners can do so through learning to speak with low‐level ESOL students, developing trauma awareness and reflexively approaching their relationships with UASCs. Thus, the article provides policy recommendations to support practitioners in doing so.